Pelatihan Media Pembelajaran Digital Untuk Guru SDN 9 Kabila - Thayban, Thayban; Munandar, Haris; Kurniawati, Erga; Sangkota, Vivi Dia Afrianti; Aris, Ayub Pratama; Pambudi, Moch Rio (Universitas Negeri Gorontalo, 2024)
Digital literacy is becoming an increasingly essential skill for educators in facing the challenges of the 21st century. This study aims to evaluate the effectiveness of digital literacy training for teachers at SDN 9 Kabila and identify the main challenges in adopting technology in education. The research employs an experimental approach through community service activities, involving stages of socialization, training, and evaluation of digital learning media implementation. A total of nine teachers actively participated in each session. The findings indicate that experiential-based training methods result in a more significant improvement in digital literacy skills compared to theoretical training alone. Teachers who engaged in interactive training, such as live demonstrations and digital learning media simulations, demonstrated better competency development than those who only received theoretical materials. This study reveals that while theoretical training provides a strong conceptual foundation, direct application in the classroom is more effective in fostering sustainable digital literacy skills.